2000
DOI: 10.1046/j.1365-2958.2000.01899.x
|View full text |Cite
|
Sign up to set email alerts
|

Targeted gene disruption in Candida albicans wild‐type strains: the role of the MDR1 gene in fluconazole resistance of clinical Candida albicans isolates

Abstract: Resistance of the pathogenic yeast Candida albicans to the antifungal agent fluconazole is often caused by active drug efflux out of the cells. In clinical C. albicans strains, fluconazole resistance frequently correlates with constitutive activation of the MDR1 gene, encoding a membrane transport protein of the major facilitator superfamily that is not expressed detectably in fluconazole‐susceptible isolates. However, the molecular changes causing MDR1 activation have not yet been elucidated, and direct proof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
153
0
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(162 citation statements)
references
References 45 publications
7
153
0
2
Order By: Relevance
“…Overexpression and gene inactivation studies have shown that MDR1 confers specific resistance to fluconazole, benomyl, cycloheximide, benzotriazole, methotrexate, 4-nitroquinoline-N-oxide (4-NQO) and sulfomethuron methyl (Ben-Yaacov et al, 1994;Fling et al, 1991;Goldway et al, 1995;Wirsching et al, 2000b). Disruption of MDR1 causes an increased susceptibility to methotrexate, cycloheximide and 4-NQO (Goldway et al, 1995;Sanglard et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression and gene inactivation studies have shown that MDR1 confers specific resistance to fluconazole, benomyl, cycloheximide, benzotriazole, methotrexate, 4-nitroquinoline-N-oxide (4-NQO) and sulfomethuron methyl (Ben-Yaacov et al, 1994;Fling et al, 1991;Goldway et al, 1995;Wirsching et al, 2000b). Disruption of MDR1 causes an increased susceptibility to methotrexate, cycloheximide and 4-NQO (Goldway et al, 1995;Sanglard et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…4,5) Several genes have been confirmed to contribute to the development of multidrug resistance including ERG11, CDR1, CDR2, MDR1, RTA2, AOX1 and AOX2. [6][7][8][9][10][11][12] Among them, upregulation of CDR1, a member of the ATP-binding cassette (ABC) transporter super-family in C. albicans, is a common occurrence in clinical C. albicans isolates resistant to antifungal azoles. 13) Cdr1p pumps azoles out of C. albicans cells to reduce intracellular accumulation, which can be indirectly identified by the efflux of rhodamine 6G (R6G), which is a fluorescent substrate transported by Cdr1p.…”
mentioning
confidence: 99%
“…The overexpression of transporter genes in A r isolates suggested that a reduced accumulation of azoles in the cell was responsible for the observed azole resistance phenotype (1,44). By using a dominant selectable marker, it was shown that deleting MDR1 from A r clinical isolates overexpressing this gene reduced the resistance of the cells to FLC, providing a direct demonstration that MDR1 is involved in clinical FLC resistance (45). However, the direct contribution of CDR1 and CDR2 to clinical azole resistance remained to be determined.…”
mentioning
confidence: 99%